(untitled) (ALPHA. Journal of Arts, Literature and Philosophy, 2018)
If we assume that “deletion of fingerprints” is one of the cruelest consequences of totalitarian practices, a political philosophy that is attentive to the consequences of totalitarian political violence will have to be responsible for the issue of “fingerprints”. The aim of this paper is to address this issue based on Benjamin´s theory of photography. In fact, we attempt to understand the final idea in the Little History of Photography when, referring to Atget‟s photographs, he reveals the political potential of photography in modern times: the reconfiguration of a crime scene where the fingerprints have been erased.